Efektivitas Sistem Informasi Akuntansi dalam Meningkatkan Transparansi dan Akurasi Laporan Keuangan UMKM - Ariza Nurro'yi; Khoriatun; Achmad Sidik; Abdur Rochman (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the effectiveness of an Accounting Information System (AIS) in improving the transparency and accuracy of financial reporting for Micro, Small, and Medium Enterprises (MSMEs). A total of 20 MSME actors participated as respondents in this research, using a quantitative approach and Spearman correlation analysis. The results show that the use of the web-based application SIAKUN significantly enhances the transparency and accuracy of MSME financial reports. There is a strong correlation between system reliability and both data accuracy and financial transparency, as well as between data accuracy and system usage effectiveness. The highest correlation was found between financial report accuracy and system usage effectiveness, indicating that a reliable and user-friendly system greatly contributes to the quality of financial reporting. This study supports previous findings emphasizing the importance of a simple, standalone, and automated accounting information system in facilitating accurate financial record-keeping. Overall, the research confirms that SIAKUN serves as a strategic solution for promoting digitalization, enhancing accountability, and strengthening the credibility of MSMEs in financial management.